DETERMINATION PROCESSES OF CRIMINAL VIOLATIONS IN THE FIELD OF TRANSPLANTATION IN RUSSIA AND UKRAINE - Babich, Dmitry Vladimirovich (International Journal of Psychosocial Rehabilitation, 2020)
The processes of crimes determination of in the field of transplantation and organs on the example of Russia and Ukraine, with consideration to the common features and ongoing political processes are discussed in the scientific article The issues of the criminal world (the underworld) development and adaptation to the changes that have occurred and are ongoing in two countries, as well as the causes of occurrence of criminal acts in this area are considered. Based on the consideration of features, specifics, and isolation, the problem of latency in the sphere of crimes of organ and tissue transplantation is considered.